2021
DOI: 10.5897/jmpr2020.7059
|View full text |Cite
|
Sign up to set email alerts
|

The study on antioxidant activity of ulvan-calcium derivative

Abstract: Ulvan is a water-soluble polysaccharide that is extracted from the algae Ulva pertusa (Chlorophyta). In this study, ulvan-calcium derivative (U-calcium) was prepared and calcium content was 5.2%. Ulvancalcium could effectively scavenge on 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis (3-ethylbenzothiazolie-6-sulfonic acid) (ABTS), hydroxyl, and superoxide radicals. The inhibition rate on superoxide radicals (•O 2-) was 83.14% at 0.2 mg/mL, and the scavenging activity of ABTS and hydroxyl radical (•OH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They show important biochemical properties, which require further investigation to understand their structure and biochemical functions. Several studies have reported the antibacterial, antifungal and antiviral properties of sulfated polysaccharides (SPs) [9][10][11], as well as their scavenging activity against superoxide, hydroxyl, DPPH (1,2-diphenylpicrylhydrazyl) and ABTS radicals [2,2′-azino-bis (3ethylbenzothiazoline-6-sulfonicacid) diammonium salt] [12,13], and they have commercial applications in food industries [14]. Moreover, the SPs from Cladophora oligoclada have been reported to have anticoagulant properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…They show important biochemical properties, which require further investigation to understand their structure and biochemical functions. Several studies have reported the antibacterial, antifungal and antiviral properties of sulfated polysaccharides (SPs) [9][10][11], as well as their scavenging activity against superoxide, hydroxyl, DPPH (1,2-diphenylpicrylhydrazyl) and ABTS radicals [2,2′-azino-bis (3ethylbenzothiazoline-6-sulfonicacid) diammonium salt] [12,13], and they have commercial applications in food industries [14]. Moreover, the SPs from Cladophora oligoclada have been reported to have anticoagulant properties [15].…”
Section: Introductionmentioning
confidence: 99%